2009
DOI: 10.1007/s10096-009-0814-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of pharyngeal and invasive emm3 Streptococcus pyogenes strains from Norway, 1988–2003

Abstract: A major virulence factor of group A streptococci (GAS) is the M protein. Strains with the M3 type are more often associated with necrotizing fasciitis (NF) and streptococcal toxic shock syndrome, and have a higher case fatality rate than strains of other M types. To better understand the epidemiology of M3 GAS strains in Norway, we analyzed 59 invasive and 69 pharyngeal isolates with respect to prophage content, allelic variation in emm3, mtsR encoding the metal transporter of Streptococcus repressor (mtsR), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
2
7
0
1
Order By: Relevance
“…Since the 1980's there has been resurgence in invasive GAS diseases in the U.S. and other parts of the world. Numerous epidemiology studies conducted in the U.S. (Stevens et al, 1989; Musser et al, 1991; Cleary et al, 1992; Johnson et al, 1992; DiPersio et al, 1996; Cockerill et al, 1997), Canada (Davies et al, 1996; Kaul et al, 1997; Sharkawy et al, 2002; Hollm-Delgado et al, 2005), and Europe (Gaworzewska and Colman, 1988; Colman et al, 1993; Lamagni et al, 2008; Meisal et al, 2010) have found associations between infections with M1- and M3-type strains and invasive diseases. Specifically, M3-type strains have been associated with severe invasive disease (Musser et al, 1991; Lamagni et al, 2008) and fatal outcomes (Gaworzewska and Colman, 1988; Colman et al, 1993; Sharkawy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980's there has been resurgence in invasive GAS diseases in the U.S. and other parts of the world. Numerous epidemiology studies conducted in the U.S. (Stevens et al, 1989; Musser et al, 1991; Cleary et al, 1992; Johnson et al, 1992; DiPersio et al, 1996; Cockerill et al, 1997), Canada (Davies et al, 1996; Kaul et al, 1997; Sharkawy et al, 2002; Hollm-Delgado et al, 2005), and Europe (Gaworzewska and Colman, 1988; Colman et al, 1993; Lamagni et al, 2008; Meisal et al, 2010) have found associations between infections with M1- and M3-type strains and invasive diseases. Specifically, M3-type strains have been associated with severe invasive disease (Musser et al, 1991; Lamagni et al, 2008) and fatal outcomes (Gaworzewska and Colman, 1988; Colman et al, 1993; Sharkawy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Dot plot analysis showed a series of parallel lines when comparing CSM sequences from M/emm 89 strains, indicating that repeat tracts (minisatellites) were present on that region, but no significant tracks of repeat patterns were observed amongst the GAS M/emm 1 and M/emm 28 strains. The motifs observed amongst the M/emm 89 strains were distinct from the patterns M3CSMR-1 and M3CSMR-2 described in Norwegian M3 strains (Meisal et al, 2010b), as shown in Fig. 1.…”
Section: Sclb Variation Amongst Randomly Selected Strainsmentioning
confidence: 69%
“…Polymorphisms on the sclB gene of Norwegian M3 strains have been proposed as potential targets for fine typing (Meisal et al, 2010b); however, the repeat region of the collagen structure motif identified amongst M3 strains from the UK were extremely large (data not shown), hindering the collection of reliable sequence data and the evaluation of the method for robustness and usefulness for subtyping UK M3 strains. Subtyping of the GAS M/emm 1 strains included in this study was not achieved as their sclB sequences were highly homogeneous, with variation observed only at the 59 region by the variable number of H091140213 H042260303 H103100035 H104380180 H102700144 H102940129 H102940131 H103000248 H103000249 H103000250 H103000251 H103000252 H103100036 H102840154 H095200180 H090520364 H102780159 H102780160 H102840153 H103340315 H103460262 H103460265 H103460266 H103540286 H103540287 H103780271 H103980138 H103980139 H104140423 H104140424 H104540321 H100500065 H094520446 H102840152 H102840156 Strain randomly selected Referral from hospital C GP patient -scalded skin presentation on neck Oubreak on maternity ward hospital C -newborn child Oubreak on maternity ward hospital C -post-partum mother Oubreak on maternity ward hospital C -post-partum mother Oubreak on maternity ward hospital C -post-partum mother Oubreak on maternity ward hospital C -post-partum mother GP patient -outbreak on maternity ward in hospital C Oubreak on maternity ward hospital C -newborn child Oubreak on maternity ward hospital C -post-partum mother Oubreak on maternity ward hospital C -newborn child GP patient -sinus behind ear discharging posterior Outbreak on elderly care ward hospital B -patient Strain randomly selected Strain randomly selected Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -patient Outbreak on elderly care ward hospital B -staff member Outbreak on elderly care ward hospital B -patient Sudden onset of ankle swelling, septic shock, renal failure, I.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations